S3 Work performance and airflow obstruction in a general UK population of older workers. (2nd December 2011) - Szram, J; Schofield, S J; Woods, A P M; Crisp, N; Harris, D; Cullinan, P
Abstract : Work disability as a consequence of COPD has been found in a number of patient cohorts and respiratory symptoms were shown to be significantly associated with work limitation in the Lungs at Work study.1 The impact of airflow obstruction on impaired work performance in the general population is unknown. The clinical assessment was designed to examine the relationship between respiratory symptoms and work performance in a general population of older workers in more detail. Volunteers in full time employment at the time of the initial postal questionnaire study (of 51 to 60-year olds through general practice) underwent clinical assessment, including spirometry (n=1773). Results are shown in Abstract S3 table 1 . Prevalence of declared doctor-diagnosed COPD was low (1.9% of men and 0.6% of women) compared to that of airflow obstruction on spirometry (post-bronchodilator FEV1 <80% predicted and FEV1 /FVC ratio<0.7) was higher, similar to previous published estimates. Men and women with airflow obstruction had a significantly higher prevalence of poor self-reported performance at work than individuals with normal spirometry. Subjects of both sexes with abnormal spirometry who also reported high levels of physical activity in their current job were significantly more likely to report poor work performance than individuals without airflow obstruction with similarly high activity levels; this difference was not seen in low activity work (data not shown). Men were significantly more likely than women to predict that they would stop work due to ill-health. In both sexes, participants with abnormal spirometry were significantly more likely to predict ill-health retirement than individuals with normal lung function. This study has demonstrated an association between airflow obstruction and both work performance within a general population of older workers; the level of physical activity required at work had an important effect on this relationship. Future loss from the workforce due to ill-health was also related to lung function. Detection of airflow obstruction could aid retention in employment, provided that suitable interventional strategies are in place to support older workers.